Nisekoi, false love Vol. 17, Mistress - Komi, Naoshi, 1986- (Viz Media, 2016)
Yui always seems to be doing a million things at school and at home, but one day, she shocks Raku by passing out, and later when the class travels to Kyoto for a school trip, Raku gets to spend some one-on-one time with his crush, Kosaki.